DFT study on the effect of functional groups of carbonaceous surface on ammonium adsorption from water. (January 2022) - Yin, Qianqian; Si, Linhui; Wang, Ruikun; Zhao, Zhenghui; Li, Heping; Wen, Zhengcheng
Abstract: Density functional theory (DFT) was used to study the adsorption of ammonium ion on carbon materials. The effects of single and multiple adjacent functional groups of carbon structures on ammonium ion adsorption were emphasized. The electrostatic potential, adsorption energy, charge transfer, molecular orbital, and dipole moment of different configurations were analyzed. Results showed that the carbonyl group was more likely to adsorb ammonium ion than lactone, carboxyl, and hydroxyl. When the carbon material contained multiple adjacent functional groups at the same time, the adsorption of ammonium ion can be promoted or inhibited due to the interaction among functional groups. The effect of functional groups on the adsorption of π bond in carbon materials was related to the electronegativity of functional groups, i.e., greater electronegativity led to smaller adsorption energy of π bond. Carbon material itself is nonpolar and hydrophobic, so adding oxygen-containing functional groups can increase the dipole moment of carbon material molecules, thereby enhancing its polarity and adsorption capacity. Graphical abstract: Image 1 Highlights: Functional groups affect the electron-cloud distribution of the carbon structure. Functional groups improve the adsorption of NH 4 + onto carbon material. Promotion or inhibition abilities exist between functional groups for NH 4 + adsorption. Carbon structure with multiple functional groups is more likely to adsorb NH 4 + .